Investigating the impact of open label design on patient‐reported outcome results in prostate cancer randomized controlled trials - Guillaume Mouillet; Fabio Efficace; Antoine Thiery‐Vuillemin; Emilie Charton; Mieke Van Hemelrijck; Francesco Sparano; Amélie Anota (Cancer Medicine, 2020)
Abstract Background While open‐label randomized controlled trials (RCT) are common in oncology, some concerns have been expressed with regard to Patient‐Reported Outcomes (PRO)‐based claims stemming from these studies. We aimed to investigate the impact of open‐label design in the context of prostate cancer (PCa) RCTs with PRO data. Methods Randomized controlled trials of PCa with a PRO endpoint published between 2004 and 2018 were considered. RCTs were systematically evaluated on the basis of previously defined criteria, including international PRO reporting quality standards and the Cochrane Collaboration's tool for assessing Risk of Bias. The rate of concordance was estimated and compared between traditional clinical outcomes (eg, survival or tumor response) and PRO in open and blinded RCTs. Results We identified 110 RCTs published between 2004 and 2018, of which 62% (n = 68) were open‐label. The general characteristics of PCa RCTs were not different according to their design (open‐label vs blinded). The proportion of PCa RCTs with high‐quality PRO reporting was not different between open‐label RCTs and blinded RCTs (41.2% vs 38.1%; P = .75). No statistically significant difference was found between PRO results and concordance with traditional clinical outcomes according to the study design. Conclusion Our findings suggest that there is no evidence of significant bias for PROs due to the absence of blinding in the context of PCa RCTs. Further analyses should be conducted in other cancer disease sites.